Plant miRNAs Reduce Cancer Cell Proliferation by Targeting MALAT1 and NEAT1: A Beneficial Cross-Kingdom Interaction - Marzano, Flaviana; Caratozzolo, Mariano Francesco; Consiglio, Arianna; Licciulli, Flavio; Liuni, Sabino; Sbisà, Elisabetta; D’Elia, Domenica; Tullo, Apollonia; Catalano, Domenico (Frontiers in Genetics, 2020)
Micro RNAs (miRNAs) are ubiquitous key gene expression regulators, evolutionarily conserved in plants and mammals. In recent years, although a growing number of papers debates the role of plant miRNAs on human gene expression, the molecular mechanisms through which this effect can be achieved are still not completely elucidated. Some evidence suggest that this interaction might be sequence-specific and, in this work, we investigated this possibility by transcriptomic and bioinformatics approaches. Plant and human miRNA sequences from primary databases were collected and selected for their similarities (global or local alignments). Out of 2,588 human miRNAs, 1,606 showed a perfect match of their seed sequence with the 5’ end of 3,172 plant miRNAs. Further selections were applied, based on the role of the human target genes or of the miRNA in cell cycle regulation (as an oncogene, tumour suppressor or biomarker for prognosis or diagnosis in cancer). Based on these criteria, 20 human miRNAs were selected as potential functional analogous of 7 plant miRNAs, that were in turn transfected in different cell lines to evaluate their effect on cell proliferation. A significant decrease was observed in all the cell lines tested, in particular in colorectal carcinoma HCT116 cell line. RNA-Seq demonstrated that 446 genes were differentially expressed 72h after transfection. Noteworthy, we demonstrated that the plant mtr-miR-5754 and gma-miR-4995 directly target the tumour-associated long non-coding RNAs MALAT1 and NEAT1 in a sequence-specific manner, respectively. In conclusion, according to other recent discoveries, our study strengthens and expands the hypothesis that plant miRNAs can exert cross-kingdom regulatory functions in mammals by targeting both protein-coding and non-coding RNA, thus suggesting new biotechnological applications.